2022
DOI: 10.1016/s2352-3018(21)00242-3
|View full text |Cite
|
Sign up to set email alerts
|

Rates of viral suppression in a cohort of people with stable HIV from two community models of ART delivery versus facility-based HIV care in Lusaka, Zambia: a cluster-randomised, non-inferiority trial nested in the HPTN 071 (PopART) trial

Abstract: Background Non-facility-based antiretroviral therapy (ART) delivery for people with stable HIV might increase sustainable ART coverage in low-income and middle-income countries. Within the HPTN 071 (PopART) trial, two interventions, home-based delivery (HBD) and adherence clubs (AC), which included groups of 15-30 participants who met at a communal venue, were compared with standard of care (SoC). In this trial we looked at the effectiveness and feasibility of these alternative models of care. Specifically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Although patient satisfaction with DSDM has not been extensively studied, some studies show similarly high levels of satisfaction (80% or higher) with community-delivery models and facility-based groups in sub-Saharan Africa [ 13 – 15 ]. A recent mixed-methods study suggested that in Uganda, some ART patients may be more satisfied with standard clinic-based care while others appreciate community-based models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although patient satisfaction with DSDM has not been extensively studied, some studies show similarly high levels of satisfaction (80% or higher) with community-delivery models and facility-based groups in sub-Saharan Africa [ 13 – 15 ]. A recent mixed-methods study suggested that in Uganda, some ART patients may be more satisfied with standard clinic-based care while others appreciate community-based models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Retention in care was defined as having received either CD4 or viral load monitoring on at least 1 occasion ≥12 months after ART initiation. People living with HIV who were on ART for at least 6 months and had a documented HIV viral load ≤1000 copies per mL were considered to be virally suppressed [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Disagreement was resolved using arbitration by a third reviewer. A total of 16 RCTs were assessed, of which seven studies had low risk, 11,14,[20][21][22][23][24] seven studies had some concerns, 12,13,[25][26][27][28] and two articles had high risk of bias. 29,30 (Figure 2).…”
Section: Quality Of the Reviewed Studiesmentioning
confidence: 99%
“…In total 1596 records were screened for inclusion, of which 16 RCTs met eligibility criteria. 10,11,13,14,[20][21][22][23][24][25][26][27][28][29][30][31] The trials included more than 13,800 PLHIV (Table 1). Most of the trials were conducted in South Africa, [12][13][14]22,23,25,29,31 with most (11 studies) conducted among adult men and women (≥18 years).…”
Section: Characteristics Of the Included Randomised Clinical Trialsmentioning
confidence: 99%